Triple‐Mode Emission of Carbon Dots: Applications for Advanced Anti‐Counterfeiting. Issue 25 (2nd May 2016) - Jiang, Kai; Zhang, Ling; Lu, Junfeng; Xu, Chunxiang; Cai, Congzhong; Lin, Hengwei
Abstract: Photoluminescence (PL), up‐conversion PL (UCPL), and phosphorescence are three kinds of phenomena common to light‐emitting materials, but it is very difficult to observe all of them simultaneously when they are derived from a single material at room temperature. For the first time, triple‐mode emission (that is, PL, UCPL, and room temperature phosphorescence (RTP)) is reported, which relies on a composite of the luminescent carbon dots (CDs) prepared from m ‐phenylenediamine and poly(vinyl alcohol) (PVA). Moreover, the CDs‐PVA aqueous dispersion is nearly colorless and demonstrates promise as a triple‐mode emission ink in the field of advanced anti‐counterfeiting. Abstract : Show me the money ! A composite comprising carbon dots exhibits three kinds of emission simultaneously: photoluminescence (PL), up‐conversion PL (UCPL), and room temperature phosphorescence (RTP). This unique feature could be applied to combat counterfeiting in the form of a printable ink with three modes of optical authentication.